PEMBINAAN ANAK-ANAK TPA SUMBER BARU DALAM MEMPERKUAT NILAI SPIRITUAL DAN KEMANDIRIAN MELALUI ISLAMIC SUPERCAMP - Al Iftitah, Ismatul Izza; Annisa Nur Firdausyi; Noormawanti; Syifa Rosada; Della Wahyu Nabilla (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2025)
This community service activity was driven by the need to foster spiritual values and independence among children at the Sumber Baru TPA as a foundation for early character development. The Islamic Supercamp program was designed to instill Islamic values, nationalism, and togetherness through engaging and participatory approaches. The method consisted of three stages: planning in collaboration with PRM, PRA, and local community leaders; implementation of activities such as moral storytelling, group exercises, art performances, evening gatherings, and traditional games involving the community; and evaluation through direct observation of children’s involvement and behavioral changes. The results showed improvements in spiritual awareness, independence, and social solidarity among the participants. The program also produced outputs such as documentation, publications, certificates, and medals. Moving forward, this initiative will be followed up with routine spiritual guidance and a continuous evaluation system to ensure sustainable positive impacts on the community.